Well-preserved boundaries: faith and co-existence in the late Ottoman Empire - Göktürk, Gülen (Birmingham Byzantine and Ottoman studies, 2020)
Ottoman tolerance reconsidered -- Maintaining boundaries: faith and co-existence In late Ottoman Cappadocia -- The path towards nationalism -- Halasane ta pragmata (things spoiled) -- Tolerating the heretics: the distinctive case of the Greek Protestants.